Dekodierung der Implizitheit des wertenden Urteils in Komplimenten (am Beispiel der cross-kulturellen Analyse von Gesprächen in männlichen geschlechtshomogenen Gruppen) - Khrystenko, Oksana (Glottotheory, 2022)
Decoding the implicitness of evaluative judgment in compliments (based on the cross-cultural analysis of conversations in male gender-homogeneneous groups). In this paper, the implicit (anti)compliments within male gender-homogeneneous groups are examined in a contrastive way. After reviewing some findings to the implicit compliments, the paper deals with a case study referring to decoding of implicit positive evaluative judgment, which constitutes a primary illocution of the compliment. The following study examines whether there are certain differences and similarities in the frequency, subject matter and phonological design of implicit (anti)compliments in [the] groups of males with different cultural backgrounds. The study also shows which contextualization cues can contribute to the decoding of the negative evaluative statement in implicit anticompliments.